GERAKAN LITERASI MEMBACA SEBAGAI PENUMBUH KREATIVITAS SISWA DI SMP NEGERI 1 SIMO - Miftah Asyrofi Muhtar; Siti Hastutik; Zurisa Evana; Main Sufanti (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Through the literacy movement, it is hoped that schools can foster student creativity, especially the ability to read and write. As in SMP Negeri 1 Simo, which implements the school literacy movement as a way to develop student creativity. The purpose of this study was to obtain data on how schools develop student creativity through reading literacy movements. This research used a qualitative case study approach, namely by collecting data from observations, interviews, document analysis, and documentation. The type of research used in this writing process is a case study that analyzes how the efforts of SMP Negeri 1 Simo to foster student creativity through reading literacy movements. The results showed: (1) the reading literacy movement at SMP Negeri 1 Simo was carried out every day before class hours began and every Friday on the 3rd week of each month, a joint literacy program was held in the schoolyard. (2) every Friday the 3rd week of each month students communicate the literacy program that has been implemented through skills, either by reading poetry, drama, then some paint together at school. (3) every 4th week students must collect the results of literacy in the form of works, then the literacy manager will carry out an assessment. If the work is good, it will be posted on the wall or on display around the school environment where a special place has been made to display / post student work. (4) with the various efforts that have been made, the school has succeeded in publishing a magazine every year. The magazine is the work of SMP Negeri 1 Simo students.